Drogas e autonomia em tempos de contrafissura - Avarca, Camila Aleixo de Campos (2021)
This thesis is the result of an intervention-research with a group of the GAM (Autonomous Medication Management) in a CAPS-AD (centre of psychosocial attention – alcohol and drugs) in the city of São Paulo, for three Years. The goal was to analyse the effects of autonomy in the gatherings of the GAM groups, from the experience of co-management of the care between professionals and participants, through talks about the heterogeneous dimensions of the lives of the participants imbricated in the relation – also multiple – with the consumption of drugs. Thus, we performed an integrative review regarding the academic production about GAM with the aim of presenting the conceptual debate on autonomy, thickening it through crossreferencing of the articles which made tracing the different voices which give theoretical support to this notion possible, as well as mapping the lines of analysis from which we benefit to communicate with the research. When we made GAM as a device to “make see and make speak”, we built three enunciative scenes which settled tensions and displacements between relations of heteronomy and effects of autonomy, such as: medicalisation of the drug consumers in the healthcare network with iatrogenic and necropolitical effects in the lives of these people; pathologization logics and practices based on Brazilian structural racism; omission about the use of drugs to guarantee better attention in health and intersectoral services, signalling meritocratic logics in care in the assistance network. Among these analysed displacements there are: individualised care actions based on the inseparability of prescribed and proscribed drugs, destabilizing speeches of truth and valuing self-care logics; practices of autonomy which produce themselves through dissensus and the affirmation of the different ways of life in the production of a “common” world, “foreigners-free”, with the drugs. In the alcohol and drugs field, the GAM poses not only as a group device that can activate displacements in the relations of heteronomy towards practices of autonomy, but it also made seen and spoken ways of producing non-anti-craving relations with drugs, stating composition with drugs and autonomy